2014
DOI: 10.1111/ajpy.12042
|View full text |Cite
|
Sign up to set email alerts
|

Parent relationships and adolescents' depression and social anxiety: Indirect associations via emotional sensitivity to rejection threat

Abstract: One prominent theory has proposed that rejection and other negative parenting practices prompt children's emotional sensitivity to the threat of rejection, often referred to as rejection sensitivity (RS). This emotional sensitivity is thought to result in social and emotional maladjustment. In the present study, we tested this model of parenting, emotional sensitivity, and maladjustment with 659 early adolescents (aged 9-13 years). The findings confirmed that adolescents who reported more negative parenting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
3
32
0
1
Order By: Relevance
“…Third, although the current study documents robust cross‐sectional associations between emotion beliefs, perceived stress, anxiety, and well‐being, we still know little about the origins and developmental course of emotion beliefs—such as the potential role that parental messages and parenting practices may play in this process (see for example Monti, Rudolph & Abaied, ; Rudolph & Zimmer‐Gembeck, , this issue). More research is also needed to better understand the causal links between emotion beliefs, perceived stress, anxiety and well‐being, and the implications these beliefs might have for psychosocial interventions and long‐term recovery.…”
Section: Discussionsupporting
confidence: 74%
“…Third, although the current study documents robust cross‐sectional associations between emotion beliefs, perceived stress, anxiety, and well‐being, we still know little about the origins and developmental course of emotion beliefs—such as the potential role that parental messages and parenting practices may play in this process (see for example Monti, Rudolph & Abaied, ; Rudolph & Zimmer‐Gembeck, , this issue). More research is also needed to better understand the causal links between emotion beliefs, perceived stress, anxiety and well‐being, and the implications these beliefs might have for psychosocial interventions and long‐term recovery.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to research on general rejection sensitivity that has shown that it is a mediator linking social adversity to symptoms of mental health problems (London et al 2007;Rudolph and Zimmer-Gembeck 2014;, heightened sensitivity in the form of greater expectations and anxiety about rejection because of physical appearance, recently labeled as appearance-based rejection sensitivity (appearance-RS), may partially explain why adverse social experiences and social anxiety are associated with greater symptoms of BDD (Fang et al 2011;Lavell et al 2014). Like BDD, appearance-RS is thought to develop from a history of victimization (Park 2007).…”
Section: Appearance-based Rejection Sensitivity As Mediatormentioning
confidence: 91%
“…Moreover, they tend to view interpersonal relationships as untrustworthy, unsafe, hostile, and threatening and may become hypervigilant and hypersensitive to rejection in other social relationships (Rohner, 2004); these experiences may lead them to feel more socially anxious. Parenting characterized by low parental warmth, high rejection, and high overprotection, are associated with youth social phobia (Knappe et al, 2009; Rudolph & Zimmer-Gembeck, 2014). Attachment theory postulates that youth, in the context of their relationships to their parents, develop attitudes and expectations that shape the formation and experience of interpersonal relationships outside of the family context (Bowlby, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Infants with ambivalent attachment at the first year of life have more social anxiety symptoms at age 11 (Bar-Haim, Dan, Eshel, & Sagi-Schwartz, 2007) and are more likely to develop anxiety disorders at age 17, after controlling for mothers’ anxiety and youth temperament (Warren, Huston, Egeland, & Sroufe, 1997). Despite the progress made linking family experiences with social anxiety, this work largely presents a narrow view of family relationships: most studies have not considered father-child relationship and mother-child relationship independently, and the influence of the broader family climate has been largely neglected (e.g., Bar-Haim et al, 2007; Rudolph & Zimmer-Gembeck, 2014). Moreover, the relationship between parenting and social anxiety may be bidirectional, but this notion remains largely untested.…”
Section: Introductionmentioning
confidence: 99%